Community, Empire and Migration - Bates, Crispin. author. aut Link
XIV, 319 p.
Keywords: South Asians in Diaspora is a collection of essays concerning the history, politics, and anthropology of migration in India, Pakistan, and Sri Lanka, as well as in the numerous overseas locations, such as Fiji, Africa, the Caribbean and USA, where South Asians migrated in the colonial period and after. It addresses the connections between migration, problems of identity and ethnic conflict from a comparative perspective, and highlights the role of shared colonial experiences in providing 'communal' solidarities and discord.